Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

How do you find the derivative of y=tan(x)y=tan(x) using first principle?

Sagot :

[tex]y=tanx\\\\y'=\lim\limits_{h\to0}\frac{tan(x+h)-tanx}{h}=\lim\limits_{h\to0}\frac{1}{h}\left(\frac{sin(x+h)}{cos(x+h)}-\frac{sinx}{cosx}\right)\\\\=\lim\limits_{h\to0}\frac{1}{h}\left(\frac{sin(x+h)cosx-sinxcos(x+h)}{cosxcos(x+h)}\right)=\lim\limits_{h\to0}\frac{sin(x+h-x)}{hcosxcos(x+h)}\\\\=\lim\limits_{h\to0}\frac{sinh}{hcosxcos(x+h)}=\left[\frac{0}{0}\right]\xrightarrow{l'Hopital's\ rule}\lim\limits_{h\to0}\frac{cosh}{cosxcos(x+h)+hcosx[-sin(x+h)]}\\\\=\frac{cos0}{cosxcos(x+0)}=\frac{1}{cos^2x}[/tex]